2007
DOI: 10.1158/0008-5472.can-06-4493
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of a Population of Mammary Gland Cells that Form Mammospheres and Have In vivo Repopulating Activity

Abstract: The identification of mammary gland stem cells (MGSC) or progenitors is important for the study of normal breast development and tumorigenesis. Based on their immunophenotype, we have isolated a population of mouse mammary gland cells that are capable of forming ''mammospheres'' in vitro. Importantly, mammospheres are enriched for cells that regenerate an entire mammary gland on implantation into a mammary fat pad. We also undertook cytogenetic analyses of mammosphere-forming cells after prolonged culture, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 21 publications
8
141
0
Order By: Relevance
“…Mammospheres are largely comprised of primitive mammary stem and progenitor cells of varying proliferation potential, and capable of undergoing both self-renewal and multilineage differentiation in vitro (Dontu et al, 2003). Moreover, transplantation of mammospheres into cleared mammary fat pad generated complete mammary structures in vivo, further confirming the presence of long-term self-renewing stem/progenitor population within mammospheres (Liao et al, 2007). Thus, unlike HMECs grown in adherent conditions that promote differentiation (Muschler et al, 1999), growth in suspension appears to enrich for mammary stem and progenitor cells.…”
Section: Introductionmentioning
confidence: 76%
“…Mammospheres are largely comprised of primitive mammary stem and progenitor cells of varying proliferation potential, and capable of undergoing both self-renewal and multilineage differentiation in vitro (Dontu et al, 2003). Moreover, transplantation of mammospheres into cleared mammary fat pad generated complete mammary structures in vivo, further confirming the presence of long-term self-renewing stem/progenitor population within mammospheres (Liao et al, 2007). Thus, unlike HMECs grown in adherent conditions that promote differentiation (Muschler et al, 1999), growth in suspension appears to enrich for mammary stem and progenitor cells.…”
Section: Introductionmentioning
confidence: 76%
“…Because increasing evidence indicates a link among basal-like tumors, the stem cell phenotype, EMT and the acquisition of tumorigenic, invasive and metastatic potential, 63 and because breast stem cells have been shown to display a basal-like phenotype with an increased expression of EMT-related genes (e.g., SLUG/SNAIL2, VIM and N-cadherin), [64][65][66][67][68][69] it might be tempting to suggest that the primary resistance to trastuzumab in the basal/HER2 subtype can be explained in terms of an intrinsic enrichment of the CSCs with EMT features. Although this suggestion might appear counterintuitive, because trastuzumab-resistant basal/HER2 cells are positive for both markers (i.e., CD44 + CD24 + ) and because of the widely accepted CD44 + CD24 -/ low mesenchymal immunophenotype of breast CSCs, it should be noted that CD24 is dynamically regulated, as recently demonstrated by Meyer et al 46 When we previously explored how trastuzumab-refractory basal/HER2+ JIMT1 cells inherently regulated the CD44 + CD24 -/low surface markers, 12 we observed that the dynamic expression of the EMT-related markers was not limited to CD44/CD24, i.e., the number of cells bearing the CD44 + CD24 -/ low mesenchymal immunophenotype switched over time from 10% in early passages to 80% in late passages.…”
Section: Discussionmentioning
confidence: 99%
“…4A). The expression pattern of these markers is a characteristic of cultured murine mammospheres capable of repopulating the entire mammary gland (33)(34)(35). As the mammospheres also expressed both p53 and ERα (Fig.…”
Section: Effects Of Estrogen and Antiestrogens Cofactor Recruitment Andmentioning
confidence: 91%